Triage for Civil Support Using Military Medical Assets to Respond to Terrorist Attacks - Cecchine, Gary (RAND Corporation, 2004)
Even before September 11, 2001, threat assessments suggested that the United States should prepare to respond to terrorist attacks inside its borders. This monograph examines the use of military medical assets to support civil authorities in the aftermath of a chemical, biological, radiological, nuclear, or conventional high explosives attack inside the United States. The authors focus on key questions, including under what circumstances military medical assets could be requested and what assets are likely to be requested.